فتاوى مجلس العلماء الإندونيسي في الأطعمة والأشربة والأدوية: دراسة تحليلية تقويمية - جفري، أحمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This research deals with some fatwas on foods, beverages and drugs co-issued by Indonesian Council of Ulama (Majelis Ulama Indonesia/ MUI) and its subsidiary body; The Assessment Institute for Foods, Drugs and Cosmetics (Lembaga Pengkajian Pangan, Obat-obatan, Kosmetik/ LPPOM-MUI). It addresses those fatwas by employing both fiqh and ushul fiqh analysis and by referring to relevant views of Muslim jurists and people of various expertise and specialities. The objective of this study is to examine the extent of the MUI's consistency with its own method of fatwa. In doing so, the research uses indispensable fiqh rulings and principles -which must be observed by mufti - pertaining foods, beverages and drugs as a benchmark. The study shows that effective cooperation between Muslim society and Ulama, and the existence of such special institute are of the utmost importance to guarantee the lawfulness of whatever people consume as well as to safeguard them from consuming whatever detrimental. Additionally, the study concludes that those fatwas are, by and large, in line with the Sharia principles and the Council itself plays important role - mainly due to collective work of Ulama and people of various expertise and specialities which is known today as collective ijtihad. The research recommends that the MUI provide more detailed fiqh explanation for each of its fatwa; by explaining the way of the reasoning, quoting the original sources, and without ignoring the consequences of the fatwa. In addition, it is important for those in the LPPOM to equip themselves with basic knowledge of Islamic science, mainly fiqh, as for those in the MUI to provision and enhance themselves with basic understanding of medicine, physics and chemistry.